Penerapan Bioinsektisida Capsicum flutescens dalam Penanganan Serangan Hama Lalat Buah (Drosophila melanogaster) - Ufafa Anggarini (LPPM Universitas Putera Batam, 2019)
The Community Partnership Program is carried out at KSM Lamor Kelud Sejahtera, Laharpang, Puncu, Kediri, East Java, through the application of Capsicum Flutescens extract as bioinsecticides to overcome fruit fly pests that attack chili commodities. The extraction was carried out by the 7 cycle sokhlet method with a percentage of product yield reaching 48.57%. Socialization and demonstration of the use of bioinsecticides have been carried out. The optimum result is obtained with a combination of natural and synthetic insecticides. Increasing the sale value of chili products is done by processing become chili powder with product packaging innovation.